Breakthrough Invasive Candida glabrata in Patients on Micafungin: a Novel FKS Gene Conversion Correlated with Sequential Elevation of MIC - Saraya, Takeshi (American Society for Microbiology, 2014)
Candida glabrata strains sequentially isolated from blood developed resistance to micafungin (MICs from <0.015 to 4 μg/ml). A novel mutation identified in micafungin-resistant strains at bp 262 of FKS2 (containing a deletion of F659 [F659del]) was inserted into the homologous region in FKS1.